Intestinal obstruction caused by tuberculosis: unmasking a silent risk - Kumari, Chandrakala; Narain, N. P. (International Journal of Research in Medical Sciences, 2024)
Background: Intestinal tuberculosis (TB) remains a global health challenge, especially in regions with a high TB prevalence. This manifestation, distinct from pulmonary TB, involves the gastrointestinal tract, often leading to intestinal obstruction. The study addresses the insidious nature of the disease, emphasizing the urgency for timely diagnosis and intervention. Recognizing the multifaceted impact of TB on various organs, the study explores the pathophysiology, clinical presentation, and diagnostic complexities of intestinal TB. Methods: This study was conducted at Nalanda medical college and hospital in Patna, Bihar, India, the retrospective study spans three years focusing on 127 patients with intestinal obstruction due to TB. Inclusion criteria prioritized histopathological confirmation of TB, ensuring cohort accuracy. The study employed preliminary investigations, including hemogram, chest X-ray, abdominal X-ray, ultrasonogram, sputum examination, and Mantoux test and CECT whole abdomen. Clinical presentations were systematically analyzed, guiding tailored management protocols based on the mode of presentation. Results: Demographically, the study identified TB as the cause in 127 cases, with a balanced gender distribution and a peak incidence in the 21-30 years age group. Presentations varied, predominantly with acute symptoms. Common complaints included abdominal pain, vomiting, constipation, and distension. Surgical intervention within 24 hours was crucial in 61.1% of cases. Intraoperatively, findings comprised mesenteric thickening, lymph nodal enlargement, and adhesions. Adhesionolysis was the primary procedure. Postoperative complications, mainly wound infections, were noted but had a limited impact on mortality. Conclusions: This study reveals TB as a significant contributor to intestinal obstruction, emphasizing challenges in early diagnosis. Adhesionolysis emerges as a key operative procedure, underscoring the need for surgical flexibility. Postoperative complications, while notable, have minimal impact on mortality.